The Golden Age of American Musical Theatre : 1943-1965. - Naden, Corinne J. (Rowman & Littlefield Pub. Group, 2011)
The Golden Age of American Musical Theatre: 1943-1965 provides synopses, cast and production credits, song titles, and other pertinent information for over 180 musicals from Oklahoma! to On A Clear Day You Can See Forever. Concentratingon a 22-year span, this book lists both commercial successes and flops of the Golden Age-when the musicals presented on Broadway showcased timeless, memorable tunes, sophisticated comedy, and the genius of creative artists like Richard Rodgers, Oscar Hammerstein, Jerome Robbins, Leonard Bernstein, George Abbott, Moss Hart, Angela Lansbury, Robert Preston, and ma.